Ni(OH)2 Nanosheet Electrocatalyst toward Alkaline Urea Electrolysis for Energy‐Saving Acidic Hydrogen Production. Issue 20 (24th October 2019) - Chen, Jingting; Ci, Suqin; Wang, Genxiang; Senthilkumar, Nangan; Zhang, Mengtian; Xu, Qiuhua; Wen, Zhenhai
Abstract: It is highly attractive to develop efficient water electrolysis route to implement hydrogen generation in a low‐cost way, which while requires excess energy to surmount the activation barriers majorly limited by oxygen evolution reaction at anode side. Herein, we report an acid‐alkali asymmetric‐electrolyte electrolyzer (AAAE) that can achieve substantial energy saving for electrolysis hydrogen generation, thanks to the assistance of electrochemical neutralization energy (ENE) and urea oxidation reaction (UOR). To this end, free‐standing Ni(OH)2 nanosheets on carbon cloth (Ni(OH)2 −NSs/CC) is fabricated as catalytic anode for alkaline UOR, which manifests impressively high catalytic activity with delivering 10 mA cm −2 at 1.32 V and long‐term durability. The as‐developed AAAE only requires an applied voltage of 0.66 V to release the electrolysis current of 10 mA cm −2, yielding the H2 Faraday efficiency close to 100 % along with H2 production rate of 183.8 μmol h −1 . Abstract : In nanotechnology we trust : A high‐performance acid‐alkali asymmetric‐electrolyte electrolyzer (AAAE) was set up to implement energy‐saving H2 generation thanks to nanotechnology advances that enable us to develop self‐supported electrodes with Ni(OH)2 nanosheets for high‐activity catalysis of urea oxidation.